1995
DOI: 10.5558/tfc71097-1
|View full text |Cite
|
Sign up to set email alerts
|

Relations among fishers, snow, and martens: Development and evaluation of two hypotheses

Abstract: Literature about the fisher (Martes pennanti) contains the folLes rtftrences faites au ptkan (Martes pennanti) soultvent lowing contradictions: (1) the species is an old-growth specialdeux contradictions: (1) l'esptce est un s#cialiste des vieilles ist versus a forest generalist, and (2) it lives with marten (M. a m rfor& par opposition B un g6ntraliste de toutes les forCts, et (2) il icana) with minimal interaction versus densities of the two vit avec un minimum d'interaction avec la martre (M. americana) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 13 publications
9
88
5
Order By: Relevance
“…In carnivores, for example, Paquet (1991) reported that coyotes did not avoid wolves during winter, and Gese et al (1996) concluded that coyotes tolerated red foxes in Yellowstone National Park during a high prey year, but not at other times. A strong abiotic affect on interactions between another pair of forest-dwelling carnivores, the marten and fisher, has been described by Krohn et al (1995). Martens, with their proportionally larger feet, can travel in deeper, softer snow than can fishers, and martens predominate in parts of Maine with deep soft snow.…”
Section: Competitionmentioning
confidence: 99%
“…In carnivores, for example, Paquet (1991) reported that coyotes did not avoid wolves during winter, and Gese et al (1996) concluded that coyotes tolerated red foxes in Yellowstone National Park during a high prey year, but not at other times. A strong abiotic affect on interactions between another pair of forest-dwelling carnivores, the marten and fisher, has been described by Krohn et al (1995). Martens, with their proportionally larger feet, can travel in deeper, softer snow than can fishers, and martens predominate in parts of Maine with deep soft snow.…”
Section: Competitionmentioning
confidence: 99%
“…The small ratio of body mass to foot area in the American marten and lynx provides this competitive advantage on snow (Krohn et al, 1995;Mowat et al, 2000;Carroll, 2007). American marten are well adapted to deep snowpacks, given their ability to tunnel into the snow to track small mammals and find warmth among tree roots.…”
Section: Introductionmentioning
confidence: 99%
“…At the regional scale (1000-10 000 km 2 ), western fisher populations generally occur in mountainous areas with extensive forest cover and low-to-moderate snowfall , Powell and Zielinski 1994, Krohn et al 1995. In California, Powell and Zielinski (1994) estimated the minimum area needed to support a viable fisher population to be at least 600 km 2 .…”
Section: Introductionmentioning
confidence: 99%